Using a Tab Review Ms Word Semantic Mapping to Write a Text - Martha Maspaitella (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Writing is often perceived as a complicated activity since it requires the writer to read and organize sentences at the same time. Therefore, someone has to go through a certain process and apply appropriate strategies in order to be able to write. One of the strategies that can be applied to improve an individual’s writing ability is semantic mapping using Tab Review MS Word. This strategy can be used to guide students, in this case, to write on a digital medium such as on the computer. By reading a particular text, students are able to determine a keyword together with its definition, make a semantic mapping, decide a topic, create a writing framework, and develop it into a piece of writing. Finally, writing is no longer a complex process, but a fun activity as the students’ motivation has increased.